Infrastructure for shared services of TSI, Inc. - So, Bronson (Animo Repository, 2009)
Shared Services is a business approach that is being widely incorporated during this period of time. It has been implemented in an enterprise level and majority of the model and studies are base on an enterprise level implementation. This includes the model and study for infrastructure development for a company. Touch Solutions, Inc., a SME (small to medium enterprises) has engaged in shared services. The company's venture out for this kind of initiative affected the infrastructure. There is a need to redefine the infrastructure to ensure measurement and cost distribution to the companies that shares TSI infrastructure. The aim is to define an infrastructure model for TSI that accommodates Shared Services. The proponents ventured in researching application Approach Model to ensure that Infrastructure services are service oriented and that the support facility of such model is applicable.